Digital Marketing, Brand Image and Customer Loyalty at Kopi Kenangan in Pekanbaru - Tarigan, Elma; Fauzi, Faradiba; Ricy, Muhammad; Wandhira, Eka; Nofirda, Fitri (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Coffee has become one of the most renowned beverages globally, particularly gaining prominence in Indonesia as a significant commodity. In recent times, the appeal of coffee has expanded among young people, particularly women, broadening its consumer base beyond its traditional audience of men and adults. With the growing popularity of coffee, coffee shop initiatives have surged, each employing various strategies to attract customers. This study aims to explore the impact of digital marketing on enhancing the brand image and customer loyalty of coffee shops, Kopi Kenangan in Pekanbaru. The qualitative research method employed a descriptive approach with case study research, incorporating surveys and interviews with employees of Kopi Kenangan in Pekanbaru. The results indicate a positive and substantial influence of digital marketing on the brand image of coffee shops, with a similarly positive and significant impact on customer loyalty.